Errors of powered swing-by in the restricted three-body problem - Ferreira, Alessandra F.S. [UNESP]; Moraes, Rodolpho V. [UNESP]; Prado, Antônio F.B.A.; Winter, Othon C. [UNESP] (American Institute of Aeronautics and Astronautics (AIAA), 2019)
The powered swing-by maneuver is described by the parameters that define the orbit of the spacecraft and the ones that define the impulse applied. In this case the impulse is applied in the periapsis of the orbit around the body used for the close approach. It is important to consider that the values of the parameters involved in this maneuver are susceptible to errors, in particular the ones relative to the impulse, which can affect the energy variation and, consequently, the orbit obtained after the maneuver. This paper has the goal of studying several aspects related to the optimization of this maneuver, particularly verifying the sensitivity of the maneuver to these parameters and the effects that their errors make in a swing-by maneuver. The errors coming from the impulsive maneuver is the most important problem when considering powered swing-by, and it is usually the main reason to avoid this technique. Therefore, this paper will study the effects of these errors and compare them with the errors due to other variables involved in the close approach. It also shows the best direction to apply the impulse, as a function of the impulse magnitude and the regions of optimality of this maneuver.